Bridging cultures in palliative care: A qualitative study of the care of Indigenous Australians with advanced illness. (April 2023) - Panozzo, Stacey; Bryan, Tamsin; Mason, Toni; Garvey, Gail; Lethborg, Carrie; Boughey, Mark; Philip, Jennifer A
Background: Lack of access, late engagement and limited referral for palliative care remain critical issues in supporting Indigenous Australians with life limiting illness. Aim: To explore the experiences and perspectives of Indigenous and non-Indigenous health professionals regarding the provision of palliative care for Indigenous people with advanced disease. Design: Qualitative study involving semi-structured focus groups/interviews with analysis following an inductive thematic approach. Setting/participants: A purposive sample ( n = 54) of medical, nursing, allied health and Indigenous Hospital Liaison Officers engaged in caring for Indigenous patients at a metropolitan teaching hospital in Australia. Results: Four overarching themes were identified regarding provision of palliative care for Indigenous patients. These were (1) the intersection of cultures – Indigenous peoples, health and palliative care, (2) bridging the cultural divide: the integral role of Indigenous Hospital Liaison Officers, (3) health professionals devolve their responsibility to provide culturally appropriate care and (4) building towards a more holistic, culturally aware provision of palliative care. Conclusions: For many Indigenous people, the health system may be experienced as inflexible, narrowly focused and even prejudiced and traumatising. For Indigenous patients at the end of life, these challenges are heightened. The Indigenous Hospital Liaison Officers, working at the intersections of these two cultures, are key to negotiating such challenges as they seek opportunities to facilitate communication and understanding between firmly held cultural needs.